Improving the Management of High-Risk Pregnancies with the Use of the Robson Classification - Mario Dias Correa Junior; Bárbara Moreira Ribeiro Trindade dos Santos; José Reinaldo Correa Roveda; Laura Carolina Menezes Vieira Silva; Larissa Silva Guimarães; Samuel Cristóvão Lopes Gonçalves (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective To analyze the rates of cesarean delivery longitudinally in a university hospital using the Robson classification. Methods Data related to births performed between 2014 and 2018 and recorded in the Maternal and Neonatal Health Information System (Sistema de Informações em Saúde Materna e Neonatal, SISMATER, in Portuguese) were analyzed using the Robson classification. As an aid, we used articles published in the last five years that approach the same topic in other Brazilian maternity hospitals; they were retrieved from the LILACS, MEDLINE, CINAHL, Scopus, Web of Science and Cochrane Library databases. Results There was little variation in the total rate of cesarean sections in the period; however, the profile of each group changed over the years. It was possible to verify a significant reduction in the participation of groups of pregnant women with lower risk and an increase in high-risk pregnancies, attributable to the decrease in beds in the institution, with a greater transfer of patients. In addition, there was a reduction in cesarean sections among the lower-risk groups,while the rate among the higher-risk groups remained stable. Conclusion The use of the Robson classification to stratify cesarean deliveries contributes to a better analysis of the indications for cesarean delivery, enabling the establishment of strategies to reduce the rates, generating a positive impact on hospital management and quality of care.